Metabolites Alteration and Antioxidant Activity of Gracilaria verrucosa After Fermentation Using Aureobasidium melanogenum MTGK.31 - Mada Triandala Sibero; Adella Maulina Savitri; Evan Hansel Frederick; Sri Sedjati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2023)
Gracilaria verrucosa is a red seaweed that has been widely utilized in the food and pharmaceutical industries due to its biological properties. The utilization of biological agents in obtaining certain bioactive compounds would confront unavoidable issues, particularly its bioactive sustainability. Hence, microbial fermentation has been reported as a practical approach to maintaining bioactive production and boosting its properties. Our study aimed to evaluate the potential of marine yeast Aureobasidium melanogenum MTGK.31 as a fermenting agent for G. verrucosa and characterize the seaweed metabolite profile and antioxidant activity after fermentation. The seaweed was fermented using A. melanogenum MTGK.31 in a medium consisting of yeast extract, peptone, and glucose. The fermentation was done for 24, 48, and 72 hours. Total plate count and pH were measured after each fermentation period. The primary and secondary metabolites of G. verrucosa in each fermentation were observed. Antioxidant assay using the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) method was conducted, followed by total phenolic content using the Folin-Ciocalteu method. It was highlighted that yeast colony increased during the fermentation, while the pH level was decreasing. We found that the fermentation not only boosted some elements in primary metabolites, but also increased G. verrucosa bioactive groups. After 72 hours of fermentation, the G. verrucosa percent radical scavenging activity (%RSA) increased more than two times compared to the fresh G. verrucosa with a %RSA value of 16.09±6.57. Nevertheless, the highest total phenolic content of 5.62±0.00028 mg GAE/g extract was shown by G. verrucosa after 48 hours of fermentation.